Mechanism and Experimental Verification of Luteolin for the Treatment of Osteoporosis Based on Network Pharmacology - Liang, Guihong; Zhao, Jinlong; Dou, Yaoxing; Yang, Yuan; Zhao, Di; Zhou, Zhanpeng; Zhang, Rui; Yang, Weiyi; Zeng, Lingfeng (Frontiers in Endocrinology, 2022)
Purpose To explore the molecular mechanism of luteolin in the treatment of osteoporosis (OP) by network pharmacological prediction and experimentation. Methods The target proteins of luteolin were obtained with the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP). OP-related proteins were extracted from the Comparative Toxicogenomics Database (CTD) and GeneCards and DisGeNET databases. We imported the common protein targets of luteolin and OP into the STRING database to obtain the relationships between the targets. The common target proteins of luteolin and OP were assessed by KEGG and GO enrichment analyses with the DAVID database. Animal experiments were conducted to verify the effect of luteolin on bone mineral density in ovariectomized (OVX) rats. Finally, the effects of luteolin on key signalling pathways were verified by cell experiments in vitro. Results Forty-four targets of luteolin involved in the treatment of OP, including key target proteins such as TP53, AKT1, HSP90AA1, JUN, RELA, CASP3, and MAPK1, were screened. KEGG enrichment analysis found that luteolin inhibits OP by regulating the PI3K-Akt, TNF, oestrogen and p53 signalling pathways. The results of animal experiments showed that bone mass in the low-dose luteolin group (Luteolin-L group, 10 mg/kg), high-dose luteolin group (Luteolin-H group, 50 mg/kg) and positive drug group was significantly higher than that in the OVX group (P<0.05). Western blot (WB) analysis showed that the protein expression levels of Collagen Ⅰ, Osteopontin and RUNX2 in bone marrow mesenchymal stem cells (BMSCs) cultured with 0.5, 1 and 5 μM luteolin for 48 h were significantly higher than those in the dimethyl sulfoxide (DMSO) group (P<0.05). In vitro cell experiments showed that the p-PI3K/PI3K and p-Akt/Akt expression ratios in BMSCs cultured with 0.5, 1 and 5 μM luteolin for 48 h were also significantly higher than those in the DMSO group (P<0.05). Conclusions Luteolin has multitarget and multichannel effects in the treatment of OP. Luteolin could reduce bone loss in OVX rats, which may be due to its ability to promote the osteogenic differentiation of BMSCs by regulating the activity of the PI3K-Akt signalling pathway.